How has the literature contributed to creating effective risk management policies in nonprofit organisations? - Santos, M. R. C. (2021)
Although risk management is critical to all sectors of society, the attention given to the business sectors initiatives in this area has obstructed the advancement of knowledge about the remaining sectors. By systematically analysing 69 academic and non-academic publications, this study sought to highlight the areas of greatest interest in the literature on non-profit organisations (NPOs). Three topics stand out more clearly: risk identification, risk management processes, and risk mitigation strategies. The first two are more likely to be discussed in academic articles, while the last topic is prevalent in non-academic publications. Two main clusters of knowledge were identified in academic articles: risk exposure and risk management strategies. This review revealed that the focus of the literature on risk has shifted from strategies for transferring risk to NPOs as risky organisations that pursue complex goals whose success depends on strategic risk management. In addition, a critical review was conducted of risk conceptualisation and characterisation and of the findings of risk studies in the non-profit sector, thereby deepening the existing understanding of the progress made in this sectors still limited application of risk management. Moreover, the similarities, divergences, and limitations of the academic and non-academic literature are addressed. Risk managements role in the non-profit sectors sustainability is an understudied subject, but this field of research can only advance if practitioners make more risk-related information available to allow academics to gather the empirically robust evidence needed to support future studies.